1976
DOI: 10.1128/iai.13.2.513-520.1976
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal scalded-skin syndrome: development of a primary binding assay for human antibody to the exfoliative toxin

Abstract: Exfoliative toxin (ET) from a phage group II Staphylococcus aureus strain causing staphylococcal scalded-skin syndrome was purified by electrofocusing. Ampholytes and salts were removed from the final product by column chromatography on G-50 Sephadex. Sodium dodecyl sulfate-polyacrylamide gels of the final product yielded a single band upon gel electrophoresis, even when 60 ,ig of protein was placed in the gels. Radiolabeling of the purified toxin with 125I yielded a product that still caused exfoliation of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Isoelectric density gradient electrophoresis. Isoelectric fractionation was performed as described previously (25). One milliliter of a concentrated Bac R. solution obtained after lyophilizing the (NH4)2SO4precipitated preparation was electrofocused for approximately 48 h at 4°C in a glycerol density gradient with 10% carrier ampholytes (Brinkmann) in the pH range of 2 to 10.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoelectric density gradient electrophoresis. Isoelectric fractionation was performed as described previously (25). One milliliter of a concentrated Bac R. solution obtained after lyophilizing the (NH4)2SO4precipitated preparation was electrofocused for approximately 48 h at 4°C in a glycerol density gradient with 10% carrier ampholytes (Brinkmann) in the pH range of 2 to 10.…”
Section: Methodsmentioning
confidence: 99%
“…The covalently closed circular structure of this large plasmid spontaneously converts to the open circular form, and this conversion is enhanced in the presence of either sodium dodecyl sulfate, Pronase, or ethidium bromide (19,24). The 56S plasmid is believed to carry at least three different types of genetic markers that include (i) a temperature-sensitive genetic site for replication, (ii) genetic loci for the production of a specific type of exfoliative toxin (ET) that is responsible for the dermatological manifestations of the staphylococcal scalded-skin syndrome (17,19,25), and (iii) a genetic site for the production of a specific bacteriocin (19,23,24) that has been designated as Bac R. in this laboratory. Genes that code for Bac R. appear to be strictly extrachromosomal, whereas genes that code for ET appear to be located both chromosomally and extrachromosomally (19).…”
mentioning
confidence: 99%
“…Of interest, Wiley et al (1976) did not observe higher titres of antibody to epidermolysin in adults as compared with children. He did recognize a smaller proportion of children who had prior exposure to this toxin as reflected by the presence of measurable antibody in their serum.…”
Section: Discussionmentioning
confidence: 72%
“…The number of healthy adults studied was small, but all but 2 of those studied had antibody present. In addition Wiley et al (1976) reported finding anti-epidermolysin antibodies by a primary binding assay in sera from 64 randomly chosen subjects of all ages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation